Improved performance of Hexacopter's roll balance control system - Al Al; Fajrin Fajrin; Asnal Effendi; Antonov Bachtiar; Aswir Premadi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
One of the obstacles in determining the constant of the proportional integral derivative (PID) control system for the stability of the Hexacopter is due to the dynamic response of the system. Changing the speed and direction of the aircraft's motion through the throttle is translated into a control system concept into a set-point change. If you have used PID control, which is constant, cannot adjust to changes in set-points or external influences, the stability and reliability of the aircraft cannot be guaranteed. This study proposes PID control, with adaptable constants, using a fuzzy logic controller (FLC). The influence of internal changes and factors outside the aircraft control system, in principle, will accumulate on the size of the error and delta-error. Thus, FLC performs tuning for the PID constant according to the error and delta-error. The design of fuzzifications and defuzzification is based on the maximum limit value of error and delta-error, and sets the value of the constant obtained by the Ziegler-Nichols method as the default value. After the real-plant test, the system performance is obtained as follows: settling time = 34mS; peak time 21mS; rise time = 9.2 mS; delay time = 5.7mS; percent overshoot and steady state error = 1%.